Knowledge, behaviour and attitudes towards Chagas disease among the Bolivian migrant population living in Japan: a cross-sectional study. Issue 9 (14th September 2020) - Iglesias Rodríguez, Inés María; Mizukami, Shusaku; Manh, Dao Huy; Thuan, Tieu Minh; Justiniano, Hugo Alberto; Miura, Sachio; Ito, George; Huy, Nguyen Tien; Smith, Chris; Hirayama, Kenji
Abstract : Objectives: This study aimed to investigate the knowledge, behaviour and attitudes towards Chagas disease (CD) among Latin American migrants in Japan and to evaluate the effectiveness of an educational activity (EA) in increasing knowledge of CD. Design: A cross-sectional, mixed-methods study employing a preknowledge and postknowledge test and focus group discussion, conducted from March 2018 to June 2018. Participants: Seventy-two participants were included, all born in Bolivia and residents in four Japanese cities. Fifty-nine of them participated in the EA. Interventions: The EA comprised showing three videos about CD and a group discussion covering different dimensions of CD and was evaluated with questionnaires to analyse the knowledge of the participants before and after. Results: Seventy-two participants were enrolled, predominantly from highly endemic CD areas of Bolivia. Though most participants were familiar with vector-borne transmission, epidemiology and symptomatology of CD, the baseline knowledge of CD was low. Less than 10% of them had been tested prior for CD. The dominant factors associated with better knowledge were living in Japan for more than 10 years (OR=8.42, 95% CI 1.56 to 48.62) and previously testing for CD (OR=11.32; 95% CI 1.52 to 105.9). The EA significantly improved the CD knowledge of the participants (p value <0.0001; 95% CI 2.32 to 3.84). The participants associated the term 'Chagas' mostly with fear and concern. The level of stigmatisation was low, in contrast to the results of other studies. The barriers encountered in care-seeking behaviour were language, the migration process and difficulties to access the healthcare system. Conclusion: EA with an integrative approach is useful to increase the knowledge of CD within the Bolivian migrant population living in Japan. The activity brings the possibility to explore not only the level of knowledge but also to reveal experiences and to understand the needs of the people at risk. Considering them as actors towards healthcare solutions could lead to better outcomes for the success of future policies and interventions aimed to decrease the global burden.